Identity Verification Standards in Welfare Programs: Experimental Evidence from India - Muralidharan, Karthik; Niehaus, Paul; Sukhtankar, Sandip (The Review of Economics and Statistics, 2025)
Abstract We study the impact of reforms that introduced more stringent, biometric ID requirements into India’s largest social protection program, using large-scale randomized and natural experiments. Corruption fell but with substantial costs to legitimate beneficiaries, 1.5–2 million of whom lost access to benefits at some point during the reforms. At the same time, adverse effects appear to have been driven primarily by decisions about the way the transition was managed, illustrating both the risks of rapid reforms, and how the impacts of promising new technologies can be highly sensitive to the protocols governing their use.